Enhanced photocatalytic H2 production of cadmium-free rGO-mediated ZnS/CuS heterojunction derived from a MOF. Issue 37 (11th September 2018) - Xu, Mei-Ling; Cui, Jian-Dong; Zhao, Jia-Hui; Liu, Fu-Tian; Li, Kui
Abstract : The MOF-templated porous ZnS/CuS heterojunction with rGO as the charge carrier mediator exhibits enhanced photocatalytic hydrogen production under visible light illumination. Abstract : A visible light-driven cadmium-free ZnS/rGO/CuS porous photocatalyst heterojunction was synthesized by simple hydrothermal and cation exchange methods using a zeolitic imidazolate framework (ZIF-8) as the template and Zn precursor. Due to the ZIF-8 templated high porous microstructure and/or the high carrier conductivity of the graphene (rGO), ZnS/CuS and ZnS/rGO/CuS heterojunctions exhibited a photocatalytic H2 -production activity 9 and 13 times larger than that of the counterpoint heterojunction derived from the inorganic precursors under visible light irradiation, respectively. This work will provide an insight into the design and synthesis of ternary composite photocatalyts with high porosity and efficient charge separation and transfer.